Breaking the Silence? The Mass Strike, Occupy Wall Street, and Demanding Jobs for All. Issue 3 (31st August 2016) - Arena, John
Abstract : The ruling class solution to the 2008 global capitalist crisis has been to restore profitability and power to capital through massive state bailouts of banks and industry combined with savage attacks on working class living standards, with Greece simply being the most advanced in the process. At the same time, a post‐2008 global mass strike emerged that provided an opportunity for a working class response to not only the latest round of attacks, but to those imposed over the three decades of the neoliberal era. In this article, I use a Luxemburgian theoretical lens to analyze the U.S.'s Occupy Wall Street component of the mass strike process. I highlight the intramovement ideological and political obstacles to advancing the mass strike process through establishing a broad set of radical, working‐class centered demands to address the crisis.